2017
DOI: 10.1111/acer.13429
|View full text |Cite
|
Sign up to set email alerts
|

Facial Curvature Detects and Explicates Ethnic Differences in Effects of Prenatal Alcohol Exposure

Abstract: Background Our objective is to help clinicians detect the facial effects of prenatal alcohol exposure (PAE) by developing computer based tools for screening facial form. Methods All 415 individuals considered were evaluated by expert dysmorphologists and categorized as 1) healthy control (HC), 2) fetal alcohol syndrome (FAS) or 3) heavily prenatally alcohol exposed (HE) but not clinically diagnosable as FAS. 3D facial photographs were used to build models of facial form to support discrimination studies. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…Smaller palpebral fissures relate to a decrease in diencephalon volume bilaterally, philtrum size correlates with volume of basal ganglia and diencephalon structures, and decreased IQ scores are associated with smaller basal ganglia structure volumes and increased physical dysmorphology features (Roussotte et al., ). Additionally, certain dysmorphological findings (i.e., orbital hypertelorism) indicate that heavy prenatal alcohol exposure during particular points in pregnancy affects brain development and ultimately results in unique facial dysmorphology (Suttie et al., ). Functional neuroimaging studies have indicated that children with FASD demonstrate altered brain activation patterns during verbal learning (Sowell et al., ), response inhibition (Fryer et al., ), visual attention (Li et al., ), and working memory (Astley et al., ; Malisza et al., ; O'Hare et al., ; Spadoni et al., ) tasks.…”
Section: Neurological Abnormalitiesmentioning
confidence: 99%
“…Smaller palpebral fissures relate to a decrease in diencephalon volume bilaterally, philtrum size correlates with volume of basal ganglia and diencephalon structures, and decreased IQ scores are associated with smaller basal ganglia structure volumes and increased physical dysmorphology features (Roussotte et al., ). Additionally, certain dysmorphological findings (i.e., orbital hypertelorism) indicate that heavy prenatal alcohol exposure during particular points in pregnancy affects brain development and ultimately results in unique facial dysmorphology (Suttie et al., ). Functional neuroimaging studies have indicated that children with FASD demonstrate altered brain activation patterns during verbal learning (Sowell et al., ), response inhibition (Fryer et al., ), visual attention (Li et al., ), and working memory (Astley et al., ; Malisza et al., ; O'Hare et al., ; Spadoni et al., ) tasks.…”
Section: Neurological Abnormalitiesmentioning
confidence: 99%
“…The Kif3a mutant mouse is a well-characterized model of genetic ciliopathy (24, 46, 73) as Kif3a mutant mice phenocopy many human ciliopathies, including hypertelorism, facial clefting, and brain abnormalities (46, 74). Similar to the defects seen in conditional Kif3a mutant mice, NAE mice can exhibit abnormal cortical hemispheres and ventral midline brain structures (13, 14) and hypertelorism has been reported in some patients with heavy prenatal alcohol exposure who lack the classic FAS facial features (4, 75). Kif3a heterozygous mice have been shown to display similar physical abnormalities, such as situs inversus, to the full knockout but at a much lower rate (76), as Kif3a -/- die by E10.…”
Section: Discussionmentioning
confidence: 66%
“…Shh transduction occurs within the axoneme of primary cilia, nearly ubiquitous structures of mammalian cells that play a particularly important role during embryonic development. Dysregulation of RVNT primary cilia poses a risk to the normal development of brain regions that arise from this area of the neural tube, namely midline structures such as the hypothalamus, septum, pituitary, and preoptic area (45), many of which have been shown to be altered by NAE Additionally, midline anomalies such as hypertelorism are a hallmark of genetic ciliopathies and have also been reported in a subset of patients with heavy prenatal alcohol exposure (4), suggesting an overlapping etiology between ciliopathies and prenatal alcohol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations